2016
DOI: 10.5114/ceji.2016.63134
|View full text |Cite
|
Sign up to set email alerts
|

Splenocyte proliferation and anaphylaxis induced by BSA challenge in a D-galactose-induced aging mouse model

Abstract: We previously found a cross-reactive autoantibody that bound to bovine serum albumin generated in a D-galactose-induced aging mouse model. Also, we confirmed that other reducing sugars (glucose and fructose) could induce the formation of autoantibody, and only following subcutaneous injection, not oral or intraperitoneal administration. Mice that had never been exposed to bovine serum albumin produced an anti-bovine serum albumin autoantibody following repeated subcutaneous injection of D-galactose (D-gal). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…It has been demonstrated that oxidative stress is one of the key factors responsibl e for liver damage and brain ageing via oxidative injury, as revealed by the over-production of the lipid peroxidation marker MDA and the increasing antioxidant activities of CAT, GSH-Px, SOD, and T-AOC. SOD is the first gatekeeper in the antioxidant defence system by catalysing the dismutation of the superoxide anion to oxygen and hydrogen peroxide (H 2 O 2 ), the latter of which is further metabolized by CAT or GSH-Px 43 45 . T-AOC is representative of all antioxidants, and MDA is well-recognized not only as an indicator of ageing but also as the most important product of membrane lipid peroxidation, and thus, it indirectly reflects the level of cell oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that oxidative stress is one of the key factors responsibl e for liver damage and brain ageing via oxidative injury, as revealed by the over-production of the lipid peroxidation marker MDA and the increasing antioxidant activities of CAT, GSH-Px, SOD, and T-AOC. SOD is the first gatekeeper in the antioxidant defence system by catalysing the dismutation of the superoxide anion to oxygen and hydrogen peroxide (H 2 O 2 ), the latter of which is further metabolized by CAT or GSH-Px 43 45 . T-AOC is representative of all antioxidants, and MDA is well-recognized not only as an indicator of ageing but also as the most important product of membrane lipid peroxidation, and thus, it indirectly reflects the level of cell oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples stood for 1 hour after collecting and were then centrifuged at 3500 r·min -1 ; then, the supernatant was kept at -20 °C until analysis. Mouse liver tissues were dissected, followed by perfusion with ice-cold phosphate buffered saline (PBS, pH 7.4) and then washing with 0.9% normal saline (1/4 w·v -1 ) to remove the blood [69]. A homogenizer was used for tissue sample homogenization in a buffer containing 10 mmol·L -1 Tris, phenylmethylsulphonyl fluoride (PMSF), and NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we observed that antibodies with cross-reactivity to BSA were produced in a D-gal-induced aging mouse model [17,18]. We performed Western blotting of mouse skin, spleen, and ovary tissue lysates with serum samples from mice that were treated with D-gal, or not, to characterize in vivo antigens bound by these antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a phenotype of a reproductive disorder, polycystic ovary syndrome (PCOS), was induced in this mouse model [16]. In sepa-rate studies, we found that autoantibodies were produced against cross-reactive bovine serum albumin (BSA) in this model [17,18]. Since then, we have focused on changes in autoantibody production and corresponding autoantigens in this mouse model.…”
Section: Introductionmentioning
confidence: 95%